(untitled) (e-Journal of Linguistics, 2026)
This research article is conducted to find out the orientational metaphor expression used in traditional marriage discourse of Manggarai speech community. Moreover, this research article wants to find out the imagery of Manggarai speech community based on the orientational metaphor expression in traditional marriage ritual. Hence, this research article used the perspective of cultural linguistic as the main theory and the orientational metaphor and discourse scenario as the supporting theory. The three theories are used and combined by the qualitative research method. Based on the source of the data, it can be concluded that there are some orientational metaphor expression that appeared in traditional marriage discourse of Manggarai speech community. The orientational metaphors expressions have the idiomatic meaning which is sourced from the imagery of Manggarai speech community. On the other hand, this research article also found the imagery that was appearing from orientational metaphor expression. Furthermore, the imagery of Manggarai speech community based on traditional marriage discourse, such as the cultural, social, magical, ideological, mythical, and biological. This research article also find out the content of traditional marriage discourse of Manggarai speech community contains the requests, hopes, and prays of the families to God and Ancestors for the bride and bridegroom, and the new family.